Role Of Financial Policy In The Economic Development Of The Republic Of Uzbekistan - Toir Rozimurodovich Kholmirzaev; Jamshid Numonovich Ziyoyev (Euro Asian Journal Publishing, 2024)
Fiscal policy plays a critical role in promoting economic development, and this is true for the Republic of Uzbekistan. The government of Uzbekistan pursues various financial policies to stimulate economic growth, attract foreign investment and improve the living standards of its citizens. This article examines the significant role of financial policy in the economic development of Uzbekistan.
Keywords: public finance; monetary policy; money circulation